PENGEMBANGAN ONE-PAGE WEBSITE KUMPULAN CERITA PENDEK ISLAMI SEBAGAI MEDIA DAKWAH KEPADA MAHASISWA - Putri Nur Ikhlas; Ilham Fauzan; Aulia Rahmawati; Ani Nur Aeni (Jurnal Al-Hikmah: Jurnal Dakwah, 2022)
This research is about a design and development of one-page website-based da'wah media for students of UPI Kampus Sumedang. This research aims to develop a da'wah media based from website 'Carrd.co' with content in the form of Islamic short stories. The use of one-page websites and short stories is considered to be able to reach various groups as well as being effective and efficient in conveying messages even in simple ways. The method used in this research is DD (Design and Development). The population taken is UPI Kampus Sumedang students from class of 2020 with a sample of 20 people. Data was collected using a questionnaire distributed online. Data analysis starts from the data collection, data presentation, data reduction, until final conclusions and content validation tests are made. Product reviews are divided into three aspects, which is design, the effectiveness of using the site and the quality of short stories. The results of the research indicate that the product is considered to have a practical design and is quite effective for use as a da’wah medium. In addition, the content presented can give a good impression to the reader. Other responses in the form of suggestions were given by respondents as evaluation material related to the design and development of this da'wah media.